The Implementation of Credit Scoring in Order to Analyze the Importance of Non Performing Loans on Peer To Peer Lending towards Credit Distribution for Micro, Small and Medium Enterprises - Hedwigis Esti Riwayati; Aviliani Aviliani; Frida Yuniar Prastika (International Business and Accounting Research Journal, 2022)
This research is motivated by an increase in the number of Micro, Small, and Medium Enterprises from year to year but it is still difficult to get access to financing in banking due to the many requirements and long process (unbankable). The existence of fintech lending companies, one of which is Peer to Peer Lending is present to answer the problem of public financial access to conventional financial institutions. This research aims to find out the influence of Non Performing Loans on Micro, Small, and Medium Enterprises Credit Distribution with the implementation of Credit Scoring as an intervening variable (Case Study on Micro, Small, and Medium Enterprise in Indonesia Period 2018-2020). The method of data collection is done by accessing data through the website of PT Amartha Mikro Fintek and the Financial Services Authority. The sample used in this study was purposive sampling with criteria that had been determined by the authors. The data obtained is then processed using Eviews 10 Software. This analysis includes statistical tests, classical assumption tests and pathway analysis tests. The results of the t-test showed that the Non Performing Loan variable had a significant negative effect on the distribution of Micro, Small, and Medium Enterprise credit. Non Performing Loan and Credit Scoring variables had not effect on the distribution of Micro, Small, and Medium Enterprise credit. Based on the track analysis test, Credit Scoring was able to mediate the influence of Non Performing Loan on Micro, Small, and Medium Enterprise credit distribution.